MDA IN THE DIAGNOSIS OF HYPOXIA IN NEWBORNS - Khaydarova Sevara (Web of Journals Publishing, 2025)
Hypoxia in newborns continues to be a major contributor to early neonatal morbidity and long-term neurological deficits. Diagnostic strategies increasingly focus on biochemical markers that indicate oxidative stress and lipid peroxidation. Among these, malondialdehyde (MDA), a stable end product of polyunsaturated fatty acid oxidation, has received particular attention due to its high reactivity and strong association with oxidative tissue injury. In this study, we examine the potential of MDA as a diagnostic marker for neonatal hypoxia, considering its biochemical origins, temporal dynamics, and methods of measurement. We also explore the relationship between elevated MDA levels and the severity of perinatal hypoxic injury. Furthermore, we discuss how MDA formation interacts with cytokine signaling, membrane destabilization, and mitochondrial dysfunction, providing an integrated perspective on the pathophysiological mechanisms underlying neonatal hypoxic states.
Keywords: Malondialdehyde, neonatal hypoxia, oxidative stress, lipid peroxidation, biomarkers, antioxidant defense, perinatal asphyxia.